Shear force responsive and fixed-point separated system for targeted treatment of arterial thrombus. (June 2021) - Zhang, Huijuan; Pei, Yamin; Gao, Linyu; He, Qingqing; Zhang, Hongling; Zhu, Ling; Zhang, Zhenzhong; Hou, Lin
Highlights: Shear force responsive and fixed-point separated NDDS to target thrombus. Sequential drug release in response to thrombus microenvironment. Efficient and safe thrombolysis under the strategy of attack-defense-protection. Graphical Abstract: ga1 Abstract: Thrombolytic treatment is the primary method for thrombotic diseases. However, uncontrollable bleeding and secondary vascular embolism are prone. Based on the thrombus microenvironment, this project constructed an "on-off " drug depot that can accurately identify thrombus and respond to changes of shear force to solve above problems. The fucoidan (Fuc)-based core-shell NPs were prepared by β-CD host-guest inclusion interaction. The thrombolytic drug urokinase (UK) and antiplatelet drug tirofiban (TI) were loaded into outer shell and inner core, respectively. In vitro and in vivo results proved that UK@Fuc-TI/PPCD was closed under low blood shear force to reduce bleeding risk. Once arriving at thrombus site, UK@Fuc-TI/PPCD can realize precise "homing" by recognizing P-selectin overexpressed by thrombus. Then sharply increased shear force at targeted thrombus broke the core-shell structure to release UK rapidly, realizing site-specific thrombolysis. Subsequently, TI loaded in PPCD core was slowly released at thrombolysis site, preventing re-embolization of blood vessels. Thrombolysis results demonstrated the in vitro thrombolysis rate of UK@Fuc-TI/PPCD pre-treated with 1000 dyne/cm 2 shear force was 91.59%. And in vivo, the percentage of residual thrombus in UK@Fuc-TI/PPCD treatment group was only 9.37% with relatively low bleeding risk, suggested this shear fore-responsive detachable system with thrombus targeting ability and sequential drug release profile can realize the efficient recanalization of embolized vessels.